2007
DOI: 10.1111/j.1365-2893.2007.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective response to Toll‐like receptor 3 and 4 ligands by activated monocytes in chronic hepatitis C virus infection

Abstract: Toll-like receptors (TLR) have a critical role in innate immunity against pathogens. We investigated the cytokine response to TLR stimulation in peripheral blood cells of subjects infected with hepatitis C virus (HCV) and/or human immunodeficiency virus (HIV) in the Women Interagency HIV Study (WIHS) cohort. Interleukin (IL)-6 in response to TLR3 and TLR4 ligands such as polyinosinic-polycytidylic acid and lipopolysaccharide was significantly compromised in HCV-infected women. High spontaneous secretion of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
6
32
1
Order By: Relevance
“…Impaired production of IL-6 by monocytes from HCV-infected patients is associated with reduced production of IL-17 by allogeneic T cells in the presence of TLR ligands. These results are supported by those of Villacres et al [28], who report a reduced IL-6 response to TLR ligands by PBMCs isolated from patients with HCV infection. They found that IL-6 production by PBMCs from patients with HCV in- fection was significantly decreased after stimulation with TLR4 ligands [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Impaired production of IL-6 by monocytes from HCV-infected patients is associated with reduced production of IL-17 by allogeneic T cells in the presence of TLR ligands. These results are supported by those of Villacres et al [28], who report a reduced IL-6 response to TLR ligands by PBMCs isolated from patients with HCV infection. They found that IL-6 production by PBMCs from patients with HCV in- fection was significantly decreased after stimulation with TLR4 ligands [28].…”
Section: Discussionsupporting
confidence: 89%
“…These results are supported by those of Villacres et al [28], who report a reduced IL-6 response to TLR ligands by PBMCs isolated from patients with HCV infection. They found that IL-6 production by PBMCs from patients with HCV in- fection was significantly decreased after stimulation with TLR4 ligands [28]. In addition, another report shows that DCs isolated from HCV-infected patients exhibit an impaired production of TNF-a in response to TLR4 ligands [29].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, via interactions with gC1qR (a surface complement receptor), the HCV core protein inhibits TLR4-induced production of IL-12 by macrophages (94). Peripheral blood monocytes taken from HCV-infected patients preferentially express IL-10 upon exposure to recombinant HCV, which may contribute to reduced T-cell responses (96) and exhibit defective responses to TLR3 and TLR4 ligands (92). It is currently not clear whether these cells are functionally impaired by the virus or whether they have adapted an altered and reversible phenotype due to external stimuli (plasticity).…”
Section: Macrophages Determine Cellular and Cytokine Milieu In Hcv-anmentioning
confidence: 99%
“…Circulating monocytes are also capable of infiltrating into the liver and serving as precursors to Kuppfer cells [36]. Upon stimulation, classical-monocytes shed CD14 [11], CD163, and produce IP-10, IL-6 and TNF [12, 14]. Here sCD14 negatively associated with CEF-specific IFNγ-response (Fig.…”
Section: Discussionmentioning
confidence: 99%